Effects of Ozone on Hippocampus BDNF and Fos Expressions in Rats with Chronic Compression of Dorsal Root Ganglia. (26th November 2021) - Zhu, Lingling; Wang, Yanxiu; Lin, Xiaowen; Zhao, Xu; Fu, Zhi jian
Abstract : The effects of ozone on hippocampal expression levels of brain-derived neurotrophic factor (BDNF) and c-fos protein (Fos) were evaluated in rats with chronic compression of dorsal root ganglia (CCD). Forty-eight adult female Sprague-Dawley rats were randomly divided into the following 4 groups (n = 12 ): sham operation (sham group), CCD group, CCD with 20  μ g/ml of ozone (CCD + A O 3 group), and CCD with 40  μ g/ml of ozone (CCD + B O 3 group). Except the sham group, unilateral L5 dorsal root ganglion (DRG) compression was performed on all other groups. On days 1, 2, and 4 after the operation, the CCD + A O 3 and CCD + B O 3 groups were injected with 100  μ l of ozone with concentrations of 20 and 40  μ g/ml, respectively. Thermal withdrawal latencies (TWLs) and mechanical withdrawal thresholds (MWTs) were measured at various time points before and after the operation. BDNF and Fos expressions were examined in the extracted hippocampi using immunohistochemistry. The TWLs and MWTs of CCD model rats that received ozone were lower with decreased BDNF and increased Fos expression levels, on day 21 after the operation, compared to those of the sham group (P < 0.05 ). The TWLs and MWTs of the CCD + A O 3 and CCD + B O 3 groups were higher with increased BDNF and decreased Fos expression levels, on day 21 after the operation, compared to those of the CCD group (P < 0.05 ). The TWLs were longer and the MWTs were higher in the CCD + B O 3 group at each time point with increased BDNF and decreased Fos expression levels, on day 21 after the operation, compared to those of the CCD + A O 3 group (P < 0.05 ). Our results revealed that ozone can relieve the neuropathic pain caused by the pathological neuralgia resulting from DRG compression in rats. The mechanism of action for ozone is likely associated with changes in BDNF and Fos expression levels in the hippocampus.